2024
DOI: 10.1109/tnsre.2024.3354806
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Self-Aligning Knee Exoskeleton With Hip Rotation Capability

Guotao Li,
Xu Liang,
Huijuan Lu
et al.

Abstract: The self-aligning capability of an exoskeleton is important to ensure wearing comfort, and the delicate motion ability of the exoskeleton is essential for motion assistance. Designing a self-aligning exoskeleton that offers improved wearing comfort and enhanced motion-assistance functions remains a challenge. This paper proposes a novel spatial self-aligning mechanism for a knee exoskeleton to enable simultaneous assistance in the flexion and extension (FE) of the knee joint and the internal and external rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Swaminathan et al, demonstrated with an ankle targeted exosuit that resistance training increases the plantar flexion torque during gait [ 18 ]. Furthermore, investigations with exoskeletons have revealed some interesting results [ 19 , 20 ]. Together, these results suggest high dosages of task-specific volitional training of the plantar flexors are vital for promoting post-stroke gait rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Swaminathan et al, demonstrated with an ankle targeted exosuit that resistance training increases the plantar flexion torque during gait [ 18 ]. Furthermore, investigations with exoskeletons have revealed some interesting results [ 19 , 20 ]. Together, these results suggest high dosages of task-specific volitional training of the plantar flexors are vital for promoting post-stroke gait rehabilitation.…”
Section: Introductionmentioning
confidence: 99%